BCI-activated electrical stimulation in children with perinatal stroke and hemiparesis: A pilot study - Jadavji, Zeanna; Kirton, Adam; Metzler, Megan J.; Zewdie, Ephrem (Frontiers in Human Neuroscience, 2023)
Background: Perinatal stroke (PS) causes most hemiparetic cerebral palsy (CP) and results in lifelong disability. Children with severe hemiparesis have limited rehabilitation options. Brain Computer Interface activated functional electrical stimulation (BCI-FES) of target muscles may enhance upper extremity function in hemiparetic adults. We conducted a pilot clinical trial to assess the safety and feasibility of BCI-FES in children with hemiparetic CP. Methods: Thirteen participants (mean age=12.2 years, 31% female) were recruited from a population-based cohort. Inclusion criteria were: (1) MRI-confirmed PS, (2) disabling hemiparetic CP, (3) age 6-18 years, (4) informed consent/assent. Those with neurological comorbidities or unstable epilepsy were excluded. Participants attended two BCI sessions: training and rehabilitation. They wore an EEG-BCI headset and two forearm stimulation electrodes. Participant’s imagination of wrist extension was classified on EEG after which muscle stimulation and visual feedback were provided when the correct visualization was detected. Results: No serious adverse events or dropouts occurred. The most common complaints were mild headache, headset discomfort and muscle fatigue. Children ranked the experience as comparable to a long car ride and none reported as unpleasant. Sessions lasted a mean of 87 minutes with 33 minutes of stimulation delivered. Mean classification accuracies were (M=78.78%, SD=9.97) for training and (M=73.48, SD=12.41) for rehabilitation. Mean Cohen’s Kappa across rehabilitation trials was M=0.43, SD=0.29, suggesting BCI competency. Conclusions: BCI-FES appears to be well tolerated and feasible in hemiparetic children. Clinical trials can now be modeled to optimize approaches and test efficacy.